Recomendaciones para el Control y Mitigación de la Marchitez del Laurel y sus Vectores, los Escarabajos Ambrosia, en Arboledas Comerciales de Aguacate en Florida - Jonathan H. Crane; Daniel Carillo; Edward A. Evans; Romina Gazis; Bruce Schaffer; Fredy Ballen; Jeff Wasielewski; Rubén Regalado (EDIS)
This is the Spanish translation of Recommendations for Control and Mitigation of Laurel Wilt and Ambrosia Beetle Vectors in Commercial Avocado Groves in Florida (HS1360). Laurel wilt and the ambrosia beetle vectors that transmit this lethal disease have and will continue to affect avocado production in Florida. At least 50% of the commercial producers are Hispanic Americans and some are more comfortable with publications in Spanish. The translator and reviewer are both previous employees of UF/IFAS.